Energy Sector Reforms and its Role of Economic Development with Special Reference to Tamilnadu - Thangamayan, S; Chithirairajan, B; Sudha, S (International Journal of Engineering and Technology, 2018)
Energy is an important input for the sustained growth of an economy. Its use by individual households and the industrial units is on the increase. Energy can be an effective weapon in the battle against poverty in a country like India. Since the days of the second five year plan of energy consideration of self-reliance as economic objectives induced the government to provide special emphasis to the development of heavy and basic industries like Iron, Steal, Heavy Machinery, Fertilizer, cement, Aluminum, Petrochemical etc. It costs about Rs.4 crore to create new generation capacity. Non-conventional source of energy being the most environment friendly, there was an urgent need to promote generation of electricity based on such sources of energy; efforts have to been made to reduce the capital cost of projects based on non-conventional and renewable sources of energy.Â